Teknik evaluasi kognitif dalam pembelajaran pendidikan agama islam di SMK Negeri 6 Surakarta - Renny Fitriana; Triono Ali Mustofa (At Turots: Jurnal Pendidikan Islam, 2023)
This study aims to determine the evaluation of learning outcomes of Islamic Religious Education, incluiding measurement techniques, assessment, and reporting of learning evaluation result of Islamic Religious Education on Cognitive Aspects in SMK Negeri 6 Surakarta. This study is a survey study with qualitative methods. Data collection techniques used are interviews, and literature studies, the source of data in this study is the teacher of Islamic Religious Education in SMK Negeri 6 Surakarta. The result of this study indicate that the evaluation of Islamic Religious Education Learning on cognitive aspects, subject teachers often do it with the form of subjective written tests. After the evaluation, the teacher will correct all the results of the leaners answers and then the teacher conducts an assessment. And from the results of the assessment, then the teacher will convey and share the test result to students while in class, as a form of joint evaluation, and can provide motivation to student